2022
DOI: 10.1117/1.jbo.27.7.076001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-segmented feature coupling for jointly reconstructing initial pressure and speed of sound in photoacoustic computed tomography

Abstract: Significance: Photoacoustic computed tomography (PACT) is a fast-growing imaging modality. In PACT, the image quality is degraded due to the unknown distribution of the speed of sound (SoS). Emerging initial pressure (IP) and SoS joint-reconstruction methods promise reduced artifacts in PACT. However, previous joint-reconstruction methods have some deficiencies. A more effective method has promising prospects in preclinical applications.Aim: We propose a multi-segmented feature coupling (MSFC) method for SoS-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Panel (b) is reproduced with permission from Ref. 113. (c)(i) Visualization of the raw transducer data.…”
Section: Acoustic Heterogeneity (Sos Mismatch)mentioning
confidence: 99%
See 1 more Smart Citation
“…Panel (b) is reproduced with permission from Ref. 113. (c)(i) Visualization of the raw transducer data.…”
Section: Acoustic Heterogeneity (Sos Mismatch)mentioning
confidence: 99%
“…Building upon the concept of feature coupling, multi-segmented feature coupling (MSFC) divides the ring array into eight subgroups. Two subgroups located at opposite sides reconstruct a region with different SOS 113 . MSFC measures the correlation coefficients between the two reconstructed images from two opposite subgroup transducers [Fig.…”
Section: Acoustic Heterogeneity (Sos Mismatch)mentioning
confidence: 99%
“…Because of its central importance to PA imaging, a variety of approaches have been proposed to tackle the problem of the unknown SoS. A spatially-varying SoS could, in principle, be recovered jointly with the PAT reconstruction, although this problem is inherently unstable and requires additional data or prior knowledge [11] , [12] , [13] , [14] , [15] , [16] , [17] . A SoS image could be found using a separate modality, such as ultrasound tomography [18] , [19] , [20] , [21] , but this requires additional time-consuming measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods were proposed to mitigate the SoS induced aberration artefacts in PA tomography [6]- [19]. In 2011, Treeby et al reported an autofocus algorithm to arrive at an optimal single SoS for the medium by iterative optimistion [6].…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, a multi-segment feature coupling (MSFC) method was developed. The full ring array was partitioned into finer groups, and the FC method was applied to each group individually to estimate a directionspecific SoS [19].…”
Section: Introductionmentioning
confidence: 99%